Activating home-visit oral health management based on community-based integrated care and its policy implications - Luna Byon (Journal of Korean Society of Dental Hygiene, 2026)
Objectives: This study aimed to examine evidence on regional disparities in home-visit oral health management and propose policy directions for national dental health programs. Methods: This study reviewed domestic literature published between 2010 and 2026, as well as government policy documents, focusing on the regional distribution of dental care resources, regional health determinants, oral health care for vulnerable populations, and the policy implications of home-visit oral health management and community-based integrated care. Results: The reviewed literature identified regional imbalances in dental resources, greater vulnerability in rural areas, and compounded barriers to dental care among individuals with limited mobility and substantial care needs. These findings suggest that home-visit oral health management may serve as a care-delivery strategy linked to community-based integrated care and professional dental referral pathways. Conclusions: To improve regional equity in oral health, public dental health policies should prioritize the allocation of resources according to regional needs, the integration of home-visit oral health management with community-based integrated care, and continuous performance evaluation.